Religiusitas dan Moderasi Beragama Gen Alpha: Komparasi antara Siswa Muslim dan Katolik di Jombang, Jawa Timur - Irwan Ahmad Akbar; M. Aliyul Wafa (Universitas Islam Negeri Imam Bonjol Padang, 2025)
This study examines the relationship between religiosity and religious moderation among Generation Alpha students in two distinct educational institutions in Jombang, Indonesia: MTs Muallimin Denanyar (Muslim) and SMP Katolik Wijana (Catholic). The study aims to explore the extent to which religiosity influences attitudes toward religious moderation and to compare these dynamics across different institutional contexts. A quantitative approach was employed, using purposive sampling to select 100 students from each school. Data were analyzed through normality and linearity tests, bivariate Pearson correlation, and Independent Samples T-Test. Findings indicate a positive and significant relationship between religiosity and religious moderation. At SMP Katolik Wijana, the correlation was moderate (r = 0.465), whereas at MTs Muallimin Denanyar it was strong (r = 0.671). Comparative analysis revealed that Muslim students exhibited higher levels of religiosity than their Catholic peers, yet both groups displayed comparable levels of religious moderation. These results suggest that personal piety does not inherently lead to exclusivist attitudes, highlighting that Generation Alpha can integrate strong religious commitment with social tolerance. The study provides empirical evidence that both educational context and social environment are critical in shaping religious moderation among Generation Alpha. These findings have implications for designing religious education curricula that balance religiosity with openness to diversity, enabling young people to function as effective agents of tolerance in multicultural societies